Assessment of Salmonella prevalence in retail ground beef in Kansas. - Estrada C., Josué D. (Zamorano: Escuela Agrícola Panamericana, 2025)
Salmonella spp. is the second leading cause of foodborne illnesses in the United States of America, particularly in meat products such as ground beef, which has a high national demand. This study evaluated the Salmonella prevalence in retail ground beef in Kansas. A total of 278 samples were obtained from 53 stores across eight cities (C1 to C8) over a four-month period, from February to May 2024. The samples were processed using the BAX® Q7 system, a real-time PCR-based method for detecting Salmonella. The results revealed an overall prevalence rate of 4%, exceeding the national average of 0.85% reported by the USDA for fiscal year 2024. Cities C2, C5, and C6 exhibited the highest prevalence rates, reaching levels of 8.1%. Additionally, five of the fifty-three stores (9.43%) reported contamination rates exceeding 6%. Although no statistically significant difference was observed between fat content and the prevalence of Salmonella (P > 0.05), the results did not indicate any dependency relating these factors to the prevalence. These findings underscore the need for improved food safety controls and ongoing surveillance at points of sale. The results represent the first steps toward developing interventions to reduce Salmonella contamination in ground beef in Kansas.